Evaluation of novel, cationic electrospun microfibrous membranes as adsorbents in bacteria removal. Issue 83 (9th September 2015) - Papaphilippou, Petri Ch.; Vyrides, Ioannis; Mpekris, Fotios; Stylianopoulos, Triantafyllos; Papatryfonos, Charalambos A.; Theocharis, Charis R.; Krasia-Christoforou, Theodora
<x xml:space="preserve">Abstract</x> Cationic, methacrylate-based electrospun microfibrous membranes have been evaluated as adsorbents for the removal of Gram-negative bacteria namely Pseudomonas aeruginosa and Advenella species from synthetic aqueous media and urban wastewater.